The level of satisfaction of the PRR sisters with religious community life and its implications to the formation program - Tadon, Maria Surat (Animo Repository, 1981)
This study made use of the descriptive survey research method in investigating the level of satisfaction of the Sisters of the Puteri Reinha Rosary (PRR) Congregation or the Daughters of the Queen of the Rosary, with their community living. Among many other factors in community life, the six factors namely: community spirit, communication, leadership, spiritual care, other human needs, and apostolate were chosen for assessing or measuring the level of their satisfaction. The instrument used for the purpose of collecting data was a questionnaire. All the respondents were Indonesian Sisters who lived in Flores and Timor Islands. All of them were professed Sisters, meaning they had made their vows or commitment to the religious life, either temporarily or for life. The implications of the findings will be used as guidelines applicable to the existing formation program of the PRR, both initial and ongoing formation. Based on the results of the study, the following conclusions were drawn: Generally speaking, all the PRR Sisters were satisfied with their religious community living, although the findings also revealed that there existed Somewhat Satisfaction in certain areas. This lack of satisfaction can be used as guidelines in reforming and renewing the formation programs or in conducting refresher courses for the PRR Sisters. Statistically, there exists a significant difference between the level of satisfaction of the Sisters with Temporary and Perpetual Vows, concerning the area of togetherness and leadership in the community. For other areas, namely, apostolate, communication, spiritual care and other human needs (physical care, recreation, etc.) there was no significant difference. Although the Sisters were satisfied, still there is a need for increasing the level of satisfaction, and the findings implied that there must be some improvement in the human basic needs, namely physical needs since this area got the lowest mean score among all variables. This is important and must be taken cared of if the Sisters w